KAJIAN PEMILIHAN SUPPLIER BEARING ASSEMBLED DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCY PROCESS (AHP) PADA PT. GV - Lokaputra, Riduwan; Wardani, Sherly ayu; Saputri, Vika Agustina; Rau, Rafli (Jurnal Sains Ilmu Teknologi Industri, 2024)
GV implements a single supplier strategy in procuring assembled bearings, this strategy creates a risk of delivery delays which has the potential to cause production stoppages. This risk can be minimized by using more than one supplier (multi supplier). Therefore, in this research a study was conducted between alternative suppliers to find out which alternative is more optimal and what standards should be used in the future in selecting a supplier of assembled bearings. The method used in this study is the Analytical Hierarchy Process. Data processing in this study uses super decision software. From data processing, the following priority scales or weights are obtained: Quality (0.39902), Delivery (0.34155), Cost (0.15162), Responsiveness (0.06747), and Flexible (0.04034). The priority of these criteria is set to become a standard for selecting supplier bearing assemblies (SOP) and used as a benchmark in assessing supplier performance. The calculation results show the weight of each alternative supplier, namely Supplier Y (0.38357), Supplier X (0.31998), Supplier Z (0.30403). From these results, supplier Y was selected as the main supplier and replacing this supplier can reduce purchasing costs and minimize delays that occurred before, this is evidenced by using supplier Y to reduce purchasing costs by Rp. 85,688,320 and the lead time required is only about 2 months.